2021
DOI: 10.1055/a-1475-4444
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Irisin and Diabetic Nephropathy in Patients with Type 2 Diabetes Mellitus: A Meta-Analysis

Abstract: Irisin, an emerging adipokine, has been involved in the pathogenesis of type 2 diabetes mellitus (T2DM). However, previous studies evaluating the association between irisin and diabetic nephropathy (DN) showed inconsistent results. We performed a meta-analysis to evaluate the above association. Matched case-control studies evaluating the difference of serum irisin between T2DM patients with and without DN were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In addition, serum irisin level has been found to be lower in patients with 1.73 m 2 GFR< 60 mL/ min compared to patients with 1.73 m 2 GFR≥ 60 mL/min (four studies). These studies show that serum irisin level may be associated with albuminuria and decreased GFR in T2DM patients (52). In our study, a negative correlation was found between irisin and GFR.…”
supporting
confidence: 68%
“…In addition, serum irisin level has been found to be lower in patients with 1.73 m 2 GFR< 60 mL/ min compared to patients with 1.73 m 2 GFR≥ 60 mL/min (four studies). These studies show that serum irisin level may be associated with albuminuria and decreased GFR in T2DM patients (52). In our study, a negative correlation was found between irisin and GFR.…”
supporting
confidence: 68%
“…Plasma irisin levels and muscular FNDC5 expression levels were reduced in patients with obesity and T2DM [47,48]. Moreover, there was an association between serum irisin and diabetic nephropathy in patients with T2DM [49]. Thus, irisin has been linked to favorable effects on metabolic diseases, such as obesity and T2DM [25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the performed statistical analysis showed that BMI, HbA1c and creatinine were the most strongly and significantly correlated with irisin concentration. Recent studies indicate the presence of a strong association between CKD and lowered irisin levels [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%